Choice of Modulation Mode and Satellite-Based Radar Altimeter Parameters - D. S. Borovitsky; A. E. Zhesterev; V. P. Ipatov; R. M. Mamchur (Известия высших учебных заведений России: Радиоэлектроника)
Satellite altimeters play a key role in Earth remote sensing programs. To attain a centimeter accuracy level within the limited energy budget the altimeter probing signal should have a processing gain of the order of tens of thousands. Un-der such circumstances both of the angle modulation modes (LFM, BPSK) are equivalent as for their tactical performance. Preference of LFM in modern foreign devices is based on the tendency to reduce demands to digital processing operation speed by transferring wide-band processing to the analog receiver part. However, modern circuitry capabilities allow to implement digital processing of the signals with the bandwidth of hundreds MHz, giving thereby the way to involving BPSK signals which are not that susceptible to various drifts and external disturbances, do not require frequency modulation super-linearity, etc. In the paper both modulation formats are compared and recommendations are given on how to choose the structure and parameters of BPSK signal.